Nucleotide sequence of the tcml gene (ribosomal protein L3) of Saccharomyces cerevisiae. - Schultz, L D (1983)
The yeast tcml gene, which codes for ribosomal protein L3, has been isolated by using recombinant DNA and genetic complementation. The DNA fragment carrying this gene has been subcloned and we have determined its DNA sequence. The 20 amino acid residues at the amino terminus as inferred from the nucleotide sequence agreed exactly with the amino acid sequence data. The amino acid composition of the encoded protein agreed with that determined for purified ribosomal protein L3. Codon usage in the tcml gene was strongly biased in the direction found for several other abundant Saccharomyces cerevisiae proteins. The tcml gene has no introns, which appears to be atypical of ribosomal protein structural genes.